The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1164/ajrccm.158.1.9710058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New, Rapid, and Quantitative D-Dimer Test in Patients with Suspected Pulmonary Embolism

Abstract: Previous studies have suggested the utility of D-Dimer ELISA assays in eliminating a diagnosis of pulmonary embolism (PE). Our objectives were to evaluate the performance of a new, rapid, quantitative, and automated Liatest D-Dimer Assay in patients with suspected PE. Three hundred eighty-six consecutive patients referred to our institution between March 1992 and December 1996 for clinically suspected PE, with recent clinical signs not exceeding 1 wk, were included in this study. Diagnosis of PE was based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 30 publications
1
32
2
2
Order By: Relevance
“…Statistical modeling (not shown) suggests that correction for verification bias might narrow the difference between the tests further. Verification bias may, however, explain why the specificities and negative predictive values in our study are somewhat lower than those reported in previous studies (5,12,15,17,38 ). Selective D-dimer testing in only the low clinical probability group could have artificially increased the exclusion rates.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Statistical modeling (not shown) suggests that correction for verification bias might narrow the difference between the tests further. Verification bias may, however, explain why the specificities and negative predictive values in our study are somewhat lower than those reported in previous studies (5,12,15,17,38 ). Selective D-dimer testing in only the low clinical probability group could have artificially increased the exclusion rates.…”
Section: Discussioncontrasting
confidence: 92%
“…On the other hand, the high falsepositive rate that has been noted for D-dimer testing may serve only to increase the number of patients evaluated for VTE, leading to increased morbidity and expense of clinical testing (27 ). Recently, several enhanced microlatex agglutination assays have become available commercially, and results of several studies of these assays appear promising (e.g., (12,17,18 ). Our study is one of the few to compare the diagnostic performance of the new Stago microlatex assay with ELISA D-dimer testing for inpatients and outpatients with suspected PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay was precalibrated and allowed a 1-time testing on an automated analyzer. 37 According to the manufacturer, the linearity of the assay ranged from 0.0 to 4.0 mg/ml. Antithrombin activity was detected based on the inhibition of thrombin using a chromogenic substrate kit.…”
Section: Default Settings and Methods Of Human Assays Applied To The mentioning
confidence: 99%
“…Eğer klinik olasılık düşük ve perfüzyon sintigrafisi de düşük olasılıklı ise pulmoner emboli tanısından uzaklaştırır. Düşük olası-lıklı sintigrafi bulguları ve yüksek olasılıklı klinik birlikte ise veya tam tersi sözkonusu ise tanı diğer yöntemlerle desteklenmelidir [3,15,16].…”
Section: Discussionunclassified